Disentangling Drivers of Meteorological Droughts in the European Greater Alpine Region During the Last Two Centuries. Issue 23 (2nd December 2019) - Haslinger, K.; Hofstätter, M.; Kroisleitner, C.; Schöner, W.; Laaha, G.; Holawe, F.; Blöschl, G.
Abstract: This study investigates the atmospheric drivers of severe precipitation deficits in the Greater Alpine Region during the last 210 years utilizing a daily atmospheric circulation type reconstruction. Precipitation deficit tends to be higher during periods with more frequent anticyclonic (dry) and less frequent cyclonic (wet) circulation types, as would be expected. However, circulation characteristics are not the main drivers of summer precipitation deficit. Dry soils in the warm season tend to limit precipitation, which is particularly the case for circulation types that are sensitive to a soil moisture‐precipitation feedback. This mechanism is of specific relevance in explaining the major drought decades of the 1860s and 1940s. Both episodes show large negative precipitation anomalies in spring followed by increasing frequencies of circulation types sensitive to soil moisture precipitation feedbacks. The dry springs of the 1860s were likely caused by circulation characteristics that were quite different from those of recent decades as a consequence of the large spatial extent of Arctic sea ice at the end of the Little Ice Age. On the other hand, the dry springs of the 1940s developed under a persistent positive pressure anomaly across Western and Central Europe, triggered by positive sea surface temperatures in the western subtropical Atlantic. Key Points: Winter and spring droughts are strongly related to the Eastern Atlantic‐Western Russia atmospheric variability pattern Summer droughts are enhanced by prevailing dry spring conditions through a positive soil moisture‐precipitation feedback The major dry episodes in the 1860s and 1940s are particularly driven by this feedback mechanism The dry springs of the 1860s were likely caused by unusual circulation regimes, synchronized with large spatial extents of Arctic sea ice at the end of the Little Ice Age The dry springs of the 1940s are due to positive sea surface temperature anomalies in the western subtropical Atlantic, which are related to a positive Eastern Atlantic‐Western Russia pattern